RAW WATER RELIABILITY ANALYSIS FOR CONTINUITY OF TEMBUDAN SPAM INTAKE (RAW WATER RELIABILITY ANALYSIS FOR THE SUSTAINABLE ENTERANCE OF THE SPAM BREAK) - Ardi Arsyad; Rabiatul Adawiyah; Sufriady Syam (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The Tembudan Drinking Water Supply System (SPAM) in Berau Regency, East Kalimantan, relies on Lake Telaga Biru as its primary raw water source with an intake capacity of 10 liters/second, currently serving 224 household connections and planned to expand to two additional villages. This study aims to evaluate the lake's reliability in meeting long-term clean water demands while considering increasing consumption and environmental risks from land clearing activities around the catchment area. A hydrological assessment was conducted using the FJ Mock method and Current Flow Meter measurements, combined with discharge analysis, storage capacity evaluation, and demand projections up to 2045. The results show that the lake's daily storage capacity reaches 16,816.85 m³, far exceeding the.